Reformulation Of Additional Criminal Law Regarding Sanctions For Defendants Of Corruption Criminal Acts In Indonesia - Chandra Purnama; Muhammad Arifin; Adi Mansar (Faculty of Law, Universitas Pekalongan, 2023)
Indonesia has Law Number 20 of 2001Jo. Law Number 31 of 1999 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption (hereinafter abbreviated as the PTPK Law). Based on Article 6 of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission. Unfortunately, the criminal provisions contained in Article 21 and Article 22 of Law No. 28 of 1999 concerning Clean and Corruption-Free State Administrators are contrary to the principles contained in the Criminal Code, namely that the Criminal Code does not use a special minimum criminal system and cumulative principal criminal penalties, so that the Criminal Code including the Criminal Procedure Code cannot be used in eradicating criminal acts of Collusion and Nepotism. In other words, violations of criminal acts of collusion and criminal acts of nepotism in our beloved country currently cannot be addressed penally based on Law No. 28 of 1999 concerning Clean and Corruption-Free State Administrators. Therefore, this law needs to be immediately updated in terms of its criminal aspects. Article 20 paragraph (7) of Law Number 31 of 1999, which states that the main punishment is only a fine with a maximum plus 1/3 (one third). The determination of this criminal fine is imperative, meaning that judges have no other choice in imposing criminal sanctions on corporations other than criminal fines